Un híbrido espontáneo entre Aristolochia gorgona y A. grandiflora (Aristolochiaceae) - Blanco, Mario (2015)
A spontaneous hybrid between Aristolochia gorgona and A. grandiflora appeared at Lankester Botanical Garden, Costa Rica, where plants of both species were cultivated in close proximity. This indicates that geographic isolation maintains the genetic integrity of these two closely related species. The flower mor- phology of A. grandiflora is dominant in the F1 hybrids. The few known cases of hybridization in the genus are listed.